The Implementation Of Spaced Repetition In Health Competency Exams Preparation A Systematic Review Of Various Models And The Impacts - Arianti Anaya; Yunia Wardi; Rino (Poltekkes Kemenkes Semarang, 2026)
Spaced repetition is a learning strategy in which material is reviewed at expanding intervals to strengthen retrieval and long-term memory. This systematic review evaluated spaced repetition in preparation for health competency examinations by examining test performance, knowledge retention, learner engagement, satisfaction, and implementation models. Searches were conducted in PubMed, ScienceDirect, Google Scholar, Scopus, Web of Science, and ERIC using Boolean combinations of